2017
DOI: 10.1177/2156587217717417
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mechanism of Anti-Inflammatory Action and Cytotoxicity of a Semipurified Fraction and Isolated Compounds From the Leaf of Peltophorum africanum (Fabaceae)

Abstract: Peltophorum africanum extracts have been shown to possess many important medicinal benefits, including anti-inflammatory and antiviral activities. However, the mechanism of action is poorly understood. The mechanism of anti-inflammatory action was determined by measuring the synthesis of cytokines in lipopolysaccharide (LPS) stimulated RAW 264.7 macrophage cells in vitro. Compound 1 (CP1), compound 2 (CP2), and fraction F3.3.0 (F3.3.0) significantly reduced the synthesis of interleukin 1β (IL-1β) from RAW 264.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Although PI sample also showed a strong NO-inhibition effect on RAW 264.7 cells after LPS stimulation, this sample was not considered as potential anti-inflammatory sources because it gave the highest cytotoxicity to the cells. Both cytotoxic and biological activities of bioactive components need to be considered because they provide an overview of the safety and efficacy of the tested compound [ 41 , 42 , 43 ]. In the anti-inflammatory screening studies, Adebayo et al [ 41 ] and Somchit et al [ 42 ] used the selectivity index (SI) to ascertain that the observed anti-inflammatory effect of the tested compound was not due to a general metabolic toxic effect on the RAW 264.7 cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Although PI sample also showed a strong NO-inhibition effect on RAW 264.7 cells after LPS stimulation, this sample was not considered as potential anti-inflammatory sources because it gave the highest cytotoxicity to the cells. Both cytotoxic and biological activities of bioactive components need to be considered because they provide an overview of the safety and efficacy of the tested compound [ 41 , 42 , 43 ]. In the anti-inflammatory screening studies, Adebayo et al [ 41 ] and Somchit et al [ 42 ] used the selectivity index (SI) to ascertain that the observed anti-inflammatory effect of the tested compound was not due to a general metabolic toxic effect on the RAW 264.7 cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The higher the value of SI, the greater the probability that the observed bioactivity (anti-inflammatory) was not as a result of metabolic toxicity of the test extracts. 1 …”
Section: Methodsmentioning
confidence: 99%
“…Cyclooxygenases and 15-LOX are the key enzymes responsible for the synthesis and release of prostanoids and eicosanoids from poly-unsaturated fatty acids (PUFAs), respectively, that exacerbate chronic inflammation and other pathogenic and allergic disorders. 1 , 2…”
Section: Introductionmentioning
confidence: 99%
“…Cells treated with DMSO served as a control. Cells were exposed to various concentrations (5,10,20,40, and 80 μM) of LBDE for 24 h. Then, 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) was dissolved in 1X PBS (5 mg/mL) and total of 50 μL was added to each well. After 2 h incubation at 37°C, total of 100 μL DMSO (Sigma) was added to dissolve the crystals in each well.…”
Section: Mtt Cell Viability Assaymentioning
confidence: 99%
“…The concentration of LBDE that reduced cell proliferation by 50% (IC50) was calculated by nonlinear regression fit using GraphPad Prism. The selectivity index (SI) was also calculated from the IC50 ratio of HEK-293 and HePG2 cells as previously shown [20,21]. SI value indicates the selectivity of the LBDE against HEK-293 and HePG2 cell lines tested.…”
Section: Mtt Cell Viability Assaymentioning
confidence: 99%